The Effect of Flash Card Media on Student Learning Outcomes in Social Studies Subjects - Arni, Yusni; Sintia, Bela; Wandira, Zeta Ulpatara; Wulandari, Septi (LPPPI Publishing, 2024)
This study is to apply the experimental method which has two variables, X and Y. The population is all students who attend SD Negeri 20 Palembang. The research sample is using two classes as experimental classes and control classes by applying pretest posttest. The way researchers collect data is with tests and documentation. Researchers carried out validity tests and reliability tests. Data analysis applies normality, homogeneity, and hypothesis testing. If the tcount value is smaller than the ttable value, then Ho will be rejected and Ha will be accepted. However, if the tcount value is equal to or greater than the ttable, then Ho will be accepted and Ha will be rejected. The results in this study are after the test obtained a significant (2-tailed) of 0.001 which is smaller than the significance level of 0.05 (5%). After being treated in the form of flash card media there was an increase in student learning outcomes in social studies subjects. It can be concluded that there is a significant effect when applying flash card media on student learning outcomes in social studies subjects. Then the alternative hypothesis is accepted and the null hypothesis is rejected.